The role of community organizations in controlling the COVID-19 pandemic in community health centers: An example from Sawah Lega, Cicalengka, Bandung Regency, West Java - Purbaningrum, Ratih Puspitaningtyas; Rahmawati, Alvina (BKM Public Health and Community Medicine, 2021)
Objective: To describe the role of community organizations in overcoming the Covid-19 pandemic in the work area of ​​the Sawah Lega Health Center, Cicalengka District, Bandung Regency, West Java. Contents: In the third week of June 2021, an increase in Covid-19 cases began in the work area of ​​the Sawah Lega Health Center with an average of 13 daily cases and reached the highest in the fourth week of June 2021, which was 42 cases. 92.5% of Covid-19 cases have mild-moderate symptoms and are required to self-isolate (isolasi mandiri, “isoman”) at home. However, health workers were overwhelmed with handling Covid-19 patients at the puskesmas and had difficulty monitoring the movement of villagers. The ratio of health workers compared to Covid-19 cases is 1:14 cases. Luckily, community organizations in the village took the initiative to share the task of helping health workers deal with Covid-19. Village officials and PKK cadres provide food to self-isolated residents. Karang Taruna members and youth posyandu cadres deliver medicine from the puskesmas, offer goods and services, monitor the progress of residents, report to the Puskesmas if any residents are showing worse symptoms, and be a liaison between the puskesmas and self-isolated residents if it is difficult to contact or don’t have a phone. In addition, they also help disinfect the village area. There is still a negative stigma among villagers on other residents who did self-isolation. Many residents still do not understand the importance of self-isolation (isolasi mandiri, ”isomanism”), so village youth are actively involved in promoting health protocols for villagers and invite residents to immediately take part in vaccines through approaches to community informal and religious leaders. WhatsApp uses in various citizen social groups. Contributions from community organizations have played a positive role in reducing Covid-19 cases in the Sawah Lega Health Center work area. Entering the second week of July 2021, the daily number of Covid-19 cases has decreased. Cross-sectoral cooperation has sped up the handling of the Covid-19 pandemic in the work area of ​​the Sawah Lega Health Center.